Air quality assessments: insights prehistoric caves can offer to our modern-day understanding - Grace N. Ijoma; Victoria Onumanyi; Khomotso Semenya (Discover Environment)
Abstract Air quality studies should integrate the assessments of cave environments with the conventional studies of indoor urban environments. Considering the rise of cave tourism and the insights these caves offer for subterranean studies, it is essential to apply knowledge from the air quality dynamics within the diverse macro-environment of cave ecosystems to progressive development of other environments. In this review, we explore how prehistoric caves, often characterized by reduced fluctuations in temperatures and isolated atmospheres, can serve as unique environments for studying air quality variations. These caves yield valuable insights into atmospheric processes that impact both the tourist experience and the sustainability of the caves themselves. We highlight recent technological advancements, such as metagenomics, which have improved the accuracy and depth of air quality studies in caves over the past decade. By reviewing key studies on cave air quality, we identify the benefits and challenges of using caves as natural laboratories, including the difficulties in accessing certain environments and the necessity for thorough chemical and microbiological analyses to gain a holistic perspective. This review emphasizes the importance of ongoing research to apply findings from cave studies to modern environmental science, particularly in developing strategies for air quality management in a changing climate.